Production and characterisation of dimeric spike truncated-nodavirus capsid displaying the receptor-binding domain of severe acute respiratory syndrome coronavirus-2 - Ho, Kok Lian; Lee, Jia Xian; Abdul Razak, Mariatulqabtiah; Tan, Wen Siang; Chan, Ming Hao (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: The COVID-19 pandemic has highlighted the essential role of vaccination, even with the availability of antiviral therapies. Although vaccines based on technologies such as mRNA, attenuated viruses, protein subunits, and adenoviral vectors have been granted emergency use approval, issues related to safety, efficacy, and production costs still exist, prompting the need for new, cost-effective, safer, and more efficient vaccine alternatives. This research focuses on evaluating the robustness of virus-like particles (VLPs) derived from the protruding domain truncated capsid protein of Macrobrachium rosenbergii nodavirus (C∆116-MrNV-CP) fused with the receptor-binding domain (RBD) of SARS-CoV-2. Materials and Methods: The RBD of SARS-CoV-2 was genetically linked to the C-terminus of C∆116-MrNV-CP to create a novel recombinant protein, C∆116-MrNV-CPRBD. The protein was expressed in Escherichia coli and purified using cation-exchange chromatography. Structural characterization was performed via scanning transmission electron microscopy (STEM) and dynamic light scattering (DLS), while its antigenicity and immunogenicity were tested using ELISA and in BALB/c mice. Results: Biophysical analysis confirmed that C∆116-MrNV-CPRBD assembled into VLPs approximately 14 nm in diameter. The RBD displayed on the surface of these VLPs was effectively recognized by an anti-RBD monoclonal antibody. Subcutaneous administration of C∆116-MrNV-CPRBD in mice demonstrated its ability to trigger both humoral and cellular immune responses. Conclusion: This study successfully engineered a VLP-based platform that presents the SARS-CoV-2 RBD on the surface of VLPs formed by a recombinant protein. The demonstrated antigenicity and immunogenicity in mice suggest that C∆116-MrNV-CP could serve as a promising platform for developing VLP-based vaccines targeting SARS-CoV-2.